pomoże ktoś? potrzebuje na teraz ;-;



Pomoże Ktoś Potrzebuje Na Teraz class=

Odpowiedź :

Maris3

Odpowiedź:

[tex]a = - 3 + ( - 1 \frac{1}{3} + 2 \div 1 \frac{1}{5} ) = - 3 + ( - 1 \frac{1}{3} + 2 \div \frac{6}{5} ) = - 3 + ( - \frac{4}{3} + 2 \times \frac{5}{6} ) = - 3 + ( - \frac{4}{3} + 1 \frac{2}{3} ) = - 3 + \frac{1}{3} = - 2 \frac{2}{3} [/tex]

[tex]b = ( \frac{1}{5} - ( - 0.3)) \times ( - 2 \frac{1}{4} - ( - 3.25)) = (0.2 + 0.3) \times ( - 2.25 + 3.25) = 0.5 \times 1 = 0.5[/tex]

[tex]b - a = 0.5 - ( - 2 \frac{2}{3} ) = \frac{1}{2} + 2 \frac{2}{3} = \frac{3}{6} + 2 \frac{4}{6} = 3 \frac{1}{6} [/tex]

b jest większe od a o [tex]3 \frac{1}{6} [/tex]